2018
DOI: 10.9734/ajarr/2018/v2i229745
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Profile of Escherichia coli Isolated from Urine of Patients in Selected General Hospitals in Abuja Municipal, Nigeria

Abstract: This study investigated the antimicrobial resistance profile of Escherichia coli from urine of patients with suspected urinary tract infections (UTIs) in selected general hospitals in Abuja Municipal, Nigeria. Four Hundred and Thirty urine samples were collected between September 2017 and May 2018 from patients attending Asokoro General Hospital (AGH), Garki Hospital Abuja (GHA) and Wuse General Hospital (WGH); and E. coli was isolated and identified by culture, microscopy and biochemical tests. The overall oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
4
6
1
Order By: Relevance
“…The isolation of E. coli from urine of suspected UTIs patients in the study centre was expected and this agree with the study earlier reported by Rami'rez-Castillo et al [14] and El-Boumri et al [15], that E. coli is one of the is the most common agent of UTIs. The percentage occurrence of the isolates in the study centre was similar with the studies earlier reported by El-Boumri et al [15] in India, Eko et al [16] in Keffi, Nigeria, Eghieye et al [2] and Rami'rez-Castillo et al [14] in Mexico. The occurrence of the isolates was higher than 12.1 % reported by Eghieye et al [2] but less than 54.0 % reported by El-Boumri et al [15].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The isolation of E. coli from urine of suspected UTIs patients in the study centre was expected and this agree with the study earlier reported by Rami'rez-Castillo et al [14] and El-Boumri et al [15], that E. coli is one of the is the most common agent of UTIs. The percentage occurrence of the isolates in the study centre was similar with the studies earlier reported by El-Boumri et al [15] in India, Eko et al [16] in Keffi, Nigeria, Eghieye et al [2] and Rami'rez-Castillo et al [14] in Mexico. The occurrence of the isolates was higher than 12.1 % reported by Eghieye et al [2] but less than 54.0 % reported by El-Boumri et al [15].…”
Section: Discussionsupporting
confidence: 89%
“…Escherichia coli are one of the most common clinically relevant and multi-drugs resistant (MDR) bacteria causing both community and hospital acquired Urinary Tract Infection (UTIs) [1]. The UTIs are one of the most common infections diagnosed in hospital setting especially in developing countries [2]. Antibiotics have been successfully used for treatment of UTIs cause by member of family Enterobacteriaceae especially E. coli [2] but emergence of strains of the isolates resistance to commonly prescribed antibiotics have been reported worldwide [2,3,4,5,6] and this however have continued to be a threat to public health due to management of this infection caused by MDR strains [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have described and characterized antibiotic-resistant urinary E. coli isolates in worldwide [11][12][13][14][15] but in the study location this report is limited, hence this study investigates antibiotic resistance profile of E. coli from the urine of Patients with suspected UTIs in Federal Medical Centre, Keffi, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Eight confirmed ciprofloxacin-resistant E. coli (CREC) isolated from urine of patients with suspected UTIs attending Garki Hospital Abuja, Nigeria (GHA) were screened in this study. The isolates, which were obtained from a recent study [20], have antibiotic resistance profiles as shown in Table 1. The isolates were maintained on nutrient agar (Oxoid Ltd, Basingstoke, UK) slants at 4ºC Refrigerator/Freezer (Model PRN 1313 HCA, BEKO, Germany); and sub-cultured on MacConkey agar (Oxoid Ltd, Basingstoke, UK) at 37ºC for 24 h to obtain pure colonies before use in experiments.…”
Section: A Bacterial Isolatesmentioning
confidence: 99%
“…No. = Number; AMC= Amoxicillin/Clavulanic Acid; AMP= Ampicillin; CTX= Cefotaxime; CAZ= Ceftazidime; CIP= Ciprofloxacin; FOX= Cefoxitin; CN=Gentamicin; IPM= Imipenem; S= Streptomycin; SXT= Sulphamethoxazole/Trimethoprim[20].…”
mentioning
confidence: 99%